2015
DOI: 10.1364/oe.23.008179
|View full text |Cite
|
Sign up to set email alerts
|

Non-spherical gold nanoparticles trapped in optical tweezers: shape matters

Abstract: We present the results of a theoretical analysis focused on three-dimensional optical trapping of non-spherical gold nanoparticles using a tightly focused laser beam (i.e. optical tweezers). We investigate how the wavelength of the trapping beam enhances trapping stiffness and determines the stable orientation of nonspherical nanoparticles in the optical trap which reveals the optimal trapping wavelength. We consider nanoparticles with diameters being between 20 nm and 254 nm illuminated by a highly focused la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 73 publications
2
27
0
Order By: Relevance
“…This result is in agreement with the previous report that the particle morphology affects the trapping forces. 11 Importantly US NPs exhibit about a two-fold reduction in the measurement error (σ rms ) for stiffness (see Table II) compared to NS counterparts due to the improved circularity of US gold NPs (see Table I). We note that when trapped with a circularly polarized beam, one can expect laserinduced rotation of gold NPs, 16 in which case the stiffness is averaged over azimuth angles.…”
Section: B Trapping In Liquidmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is in agreement with the previous report that the particle morphology affects the trapping forces. 11 Importantly US NPs exhibit about a two-fold reduction in the measurement error (σ rms ) for stiffness (see Table II) compared to NS counterparts due to the improved circularity of US gold NPs (see Table I). We note that when trapped with a circularly polarized beam, one can expect laserinduced rotation of gold NPs, 16 in which case the stiffness is averaged over azimuth angles.…”
Section: B Trapping In Liquidmentioning
confidence: 99%
“…2 This experimental result was revisited by a recent study including a theoretical model based on the coupled dipole method. 11 The model suggests that particles larger than 170 nm can be stably trapped only if they deviate from a perfect spherical shape, which is commonly assumed for gold NPs. Indeed, scanning electron microscopy has revealed that commercially available gold NPs are inherently non-spherical and rather appear in the shape of icosahedron, decahedron, triangular, or hexagonal prism structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brzobohatý et al (2015b) used simulations to explore the shape dependence of the trapping behaviour of nonspherical gold nanoparticles. Brzobohatý et al (2015a) used simulations to support experiments rotational dynamics of multiple spheroidal particles in a dual beam trap.…”
Section: Applications Of Simulationsmentioning
confidence: 99%
“…Optical tweezers are commonly used for trapping and manipulation with micro-and nanoparticles [1][2][3][4]. Since their invention in 1986, the field of optical trapping has become a hot-spot topic for research, and its applications have extended from microfabrication [5] to drug delivery [6].…”
Section: Introductionmentioning
confidence: 99%